PENINGKATAN PERILAKU PENCEGAHAN DAMPAK PESTISIDA PADA KESEHATAN PETANI - Gracia Victoria Souisa; Bellytra Talarima; Zasendy Rehena (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
Permasalahan dari kelompok petani sayur di Desa Waiheru, Kecamatan Baguala, Kota Ambon yaitu pengetahuan dan kesadaran yang masih rendah berdampak pada kurangnya perilaku pencegahan dampak akibat penggunaan pestisida seperti kurangnya praktik penggunaan alat pelindung diri oleh petani ketika melakukan penyemprotan. Tujuan Program Kemitraan Masyarakat adalah membantu meningkatkan pengetahuan dan pemahaman tentang perilaku pencegahan dampak penggunaan pestisida bagi komunitas petani di Desa Waiheru, pendampingan dalam pembuatan buku panduan/ pedoman perilaku pencegahan dampak pestisida, dan pemeriksaan hemoglobin pada petani sebagai indicator paparan pestisida kimia. Metode yang digunakan adalah pendampingan, penyuluhan/ sosialisasi, pemutaran video, penempelan poster, pemeriksaan hemoglobin. Hasil yang didapatkan adalah 1). Adanya peningkatan pengetahuan petani yaitu untuk nilai baik (≥ 70) dari 8 orang (66,7 % - pretest) menjadi 12 orang (100% - posttest); 2). sebanyak 3 (18,8%) petani yang mengalami abnormalitas hemoglobin (lebih rendah dari nilai normal); 3). Terlaksananya pemutaran video dan pemasangan poster penggunaan APD di Walang Tani. Kesimpulan dari kegiatan ini adalah kegiatan penyuluhan, pemasangan poster, pemutaran video dan pemeriksaan hemoglobin telah meningkatkan pengetahuan petani tentang perilaku pencegahan dampak kesehatan akibat penggunaan pestisida dan memberikan gambaran kesehatan petani.Kata kunci: Pemeriksaan Kesehatan; Penyuluhan; Komunitas Petani.AbstractCommunity service activities at the vegetable farming community in Waiheru Village, Baguala Subdistrict, Ambon, were carried out based on problems from the partner groups, namely the low level of knowledge and awareness of the impact on the lack of impact prevention behavior due to the use of pesticides from farmers such as misconduct when spraying; lacking of technical guidelines / guidelines on the application of pesticide impact prevention behavior; the existence of health problems in pesticide spraying farmers such as itching and nausea after spraying pesticides; also the lacking of practice of using personal protective equipment by farmers when spraying. Farmers need assistance and counseling to increase knowledge. Counseling conducted by agricultural extension has not touched by many aspects of the health of farmers regarding the use of pesticides. The aim of the Community Partnership Program is to help increasing the knowledge and understanding of the behavior of preventing the use of pesticides for the farming community in Waiheru Village, assistance in making manuals / guidelines for preventing pesticide impacts, and examining hemoglobin in farmers as indicators of chemical pesticide exposure. The methods used to achieve the objectives are assistance, counseling / socialization, video screenings, poster placement, hemoglobin examination. The results obtained are 1). An increase in farmers' knowledge is for good grades (≥ 70) from 8 people (66.7% - pretest) to 12 people (100% - posttest); 2).The amount are 3 (18.8%) farmers experienced hemoglobin abnormalities (lower than normal values); 3). The implementation of video screenings and posters for the use of PPE in Walang Tani. The conclusion is the activities of counseling, posting posters, video screenings and hemoglobin examinations have increased the knowledge of farmers about preventing health effects due to the use of pesticides and provide an overview of farmers' health.Keywords: Health Check; Counseling; Farming Community.